Analisis Yuridis Omnibus Law dalam Hukum Ketenagakerjaan di Indonesia - Diah Anggraeni Novitasari; Kunarto Kunarto (Prosiding Seminar Nasional Ilmu Hukum, 2024)
The law’s rules that set about the employment in Indonesia run into many problems which have an impact to the imbalance investment in Indonesia. To increase the investment, the DPR formed Law No. 11 of 2020 that concerning job creation which simplifies and give the rules details that related with the employment by using the omnibus law technique. Throw back to the year before, the laws that contains about the employment has been created through Law No. 13 of 2013 that has been simplified from six ordinances and nine related laws. But in the implementation, Law No. 13 of 2013 has been acommodated many interests and spent a lot of time and money. Comparing with the Law No. 11 of 2020 about the job creation, discussion regarding the laws did not spend a lot of time because it already planned by several part which is when the laws has been released raises a lot of judicial riview.